PROBABILISTIC ANALYSIS FOR SCHMIDT FACTOR OF POLYCRYSTALS - ZHOU JinYu; ZHU FuXian; CHEN Zhen (Jixie qiangdu)
Schmidt factor of polycrystals is an important variable of structure fatigue life analysis. On the meso-scale,for textured and untextured polycrystalline,relationships between Schmidt factor and stochastic Euler angles of grains orientation are discussed respectively,the fact that face-centered and body-centered crystals with the same orientation presenting the same Schmidt factor is proved,the meso-scale probabilistic model of Schmidt factor is built,and the statistical simulation based on meso-scale is executed. The probabilistic distribution of the Schmidt factor of grains group in fatigue crack initiation zone is obtained,which can provide theoretical basis and effective engineering method for fatigue reliability analysis of the mechanical structure,especially micromechanical and micro electromechanical structures.